Multifunctional coupling super-slip anti-icing coating and preparation method thereof
A multifunctional super-slip anti-icing coating using titanium carbide and hollow glass microspheres with lubricating fillers addresses SLIPS' maintenance issues, ensuring durable and efficient anti-icing performance across diverse conditions.
Patent Information
- Application Number
- CN202411402233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing super-slippery lubricated surfaces (SLIPS) for anti-icing suffer from sacrificial lubricant loss, environmental hazards, and performance degradation due to impurities, requiring constant maintenance and economic inefficiency.
A multifunctional coupled super-slip anti-icing coating composed of titanium carbide nanoparticles, hollow glass microspheres, and lubricating fillers, with a formulation that includes stearic acid, silanes, and epoxy resin, providing excellent adhesion, durability, and electrical conductivity, achieved through a hydrothermal reaction and coating process.
The coating maintains low ice adhesion and super-slip properties under multiple deicing cycles, with high light absorption, self-cleaning, and adaptability to various liquids, ensuring effective anti-icing performance and durability in harsh environments.
Smart Images

Figure CN119192947A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material surface treatment and surface anti-icing, and in particular to a multifunctional coupled super-slip anti-icing coating and a preparation method thereof. Background Art
[0002] In the field of anti-icing, research focusing on superhydrophobic photothermal anti-icing coatings has received widespread attention. However, superhydrophobic surfaces also have some inherent defects in the field of deicing. Especially under ultra-low temperature and high humidity conditions, condensed micro-ice droplets will first appear on the micro-nanostructure of the surface, causing the "air cushion" in the micro-nanostructure to be destroyed. When the growth of micro-ice droplets extends to the surface, the mechanical interlocking effect formed between the micro-droplets and the surface will trigger an apparent pinning effect, which increases the adhesion between ice and the surface, causing the failure of the macroscopic anti-icing function of the surface (L. Gong, W. Yang, Y. Sun, C.Zhou, F. Wu, H. Zeng, Adv. Funct. Mater. 2023,2214947.). Therefore, inspired by the super-slippery phenomenon of the pitcher plant surface, using oily substances with low surface energy infiltrated on the substrate to prepare a porous infiltrated lubricated surface (SLIP) with dynamic oil film characteristics is another technical path to achieve the anti-icing function.
[0003] Compared to the water-solid contact interface of traditional superhydrophobic surfaces, the contact interface between the SLIPS surface and water droplets belongs to the water-oil contact interface. With the opposite polarity and immiscible principle of oil and water, the water-oil interface has the advantage of extremely low contact angle hysteresis, which allows water droplets to slide off the surface at a smaller angle and cannot infiltrate the micro-nanoscale structure of the surface. Therefore, the SLIPS surface has a smaller ice adhesion strength than the superhydrophobic surface, and exhibits excellent anti-icing / anti-icing performance under high humidity conditions.
[0004] Although the SLIPS surface has obvious structural advantages in the field of low ice adhesion, its own defects also need attention and improvement. The problems with the SLIPS surface are: the lubricating layer on the surface is a sacrificial coating. As the number of surface deicing cycles increases, the thickness of the oil film continues to decrease, and the low ice adhesion gradually weakens until it is lost; the failed SLIPS surface can restore some performance by refilling the lubricating fluid, but it still needs constant maintenance and the economic performance is greatly reduced; the lost oil lubricating layer may pose a hazard to the environment and organisms; the SLIPS surface will also have problems such as adsorption of impurities and dust, resulting in a decrease in the performance of low ice adhesion (Z. Tong, L. Song, S. Chen, J. Hu, Y. Hou, Q. Liu, Y. Ren, X. Zhan, Q. Zhang, Adv. Funct. Mater. 2022, 32, 2201290.).
[0005] In order to overcome the above problems, the super-slip surface utilizes the strong adhesion between the substrate and the lubricating filler to greatly reduce the loss of the surface lubricant, thereby ensuring the super-slip properties of the surface and the low ice adhesion properties. The Chinese invention patent (application publication number CN 113801535 A) "A coating for preparing a super-slip coating and its application" applied by Song Jinlong et al. uses a simple solute solvent mixing process to prepare a super-slip coating with high anti-stick properties, high bonding strength with the substrate and good durability. However, there are no reports on multifunctional coupled super-slip anti-icing coatings. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a multifunctional coupled super-slip anti-icing coating with good electrical conductivity and durability.
[0007] Another technical problem to be solved by the present invention is to provide a method for preparing the multifunctional coupled super-slip anti-icing coating.
[0008] To solve the above problems, the present invention discloses a multifunctional coupled super-slip anti-icing coating, characterized in that the coating is composed of the following raw materials in parts by weight: 10 to 21 parts of titanium carbide nanoparticles, 20 to 40 parts of epoxy resin, 1 to 5 parts of stearic acid solution, 10 to 21 parts of hollow glass microspheres, 1 to 5 parts of 1H, 1H, 2H, 2H-perfluorododecyltriethoxysilane, 1 to 5 parts of tetraethyl orthosilicate, 10-20 parts of lubricating filler, 0.1 to 1 part of leveling agent, 0.1 to 1 part of dispersant, 0.1 to 1 part of defoaming agent, 2 to 4 parts of curing agent, 30 to 70 parts of solvent and 30 to 70 parts of anhydrous ethanol solution.
[0009] The titanium carbide nanoparticles are transition metal carbides with a particle size of 40-100 nm, a cubic crystal form, and a specific surface area of 20-65 m 2 / g, volume density is 0.15~0.56g / cm 3 The hollow glass microspheres are inorganic fillers with a particle size of 10-20 μm and a density of 0.12-0.60 g / cm 3 The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 10~50 cs.
[0010] The mass concentration of the stearic acid solution is 10-20 mmol / L.
[0011] The leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and EFKA 2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184.
[0012] The solvent is one or more of anhydrous ethanol, acetone and ethyl acetate.
[0013] The light absorption rate of the coating in the 0.3~2.5μm solar light band is >96%, and the water contact angle of the coating surface is >100°, the water rolling angle is <5°, and the ice adhesion is <10 kPa.
[0014] The method for preparing the multifunctional coupled super-slip anti-icing coating as described above comprises the following steps: ⑴Weigh according to the ratio; (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add titanium carbide nanoparticles, hollow glass microspheres, 1 / 2 of the total amount of stearic acid solution, 2 / 5 of the total amount of ethyl orthosilicate, and 1 / 2 of the total amount of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to anhydrous ethanol solution, stir magnetically at a speed of 400 r / min for 120 to 180 min at room temperature, and perform ultrasonic stirring for 30 to 60 min after stirring to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② The titanium carbide-hollow glass microsphere composite functional particle suspension is transferred to a hydrothermal reaction kettle, the hydrothermal reaction temperature is 180-240° C., and the reaction time is 240-360 min, to obtain a composite functional particle solution after the hydrothermal reaction; ③ The composite functional particle solution after the hydrothermal reaction is filtered to retain the precipitate at the bottom; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained; ⑶ Add titanium carbide-hollow glass microsphere composite functional particles, the remaining stearic acid solution, 3 / 10-7 / 5 of the total amount of ethyl orthosilicate, the remaining 1H,1H,2H,2H-perfluorododecyltriethoxysilane, lubricating filler, and 1 / 2 of the total amount of curing agent to 1 / 2 of the total amount of the solvent, and stir at a speed of 600-800 r / min for 360-420 min to obtain a mixed suspension component A; (4) Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, stir at a speed of 400-600 r / min for 120-180 min to obtain a mixed suspension component B; (5) Mixing the mixed suspension component A with the mixed suspension component B and other components, and sequentially adding a leveling agent, a dispersant, a defoaming agent, and the remaining curing agent, and ball milling in a planetary ball mill for 120 to 180 minutes to obtain an ultra-slip anti-icing suspension solution under all-weather conditions; (6) The super-slip anti-icing suspension solution is evenly sprayed or spin-coated on the surface-treated substrate to obtain a wet film with a thickness of 160-220 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 100-160 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0015] The spraying conditions in step (6) are as follows: a low-pressure spray gun is used with a nozzle diameter of 1.5 mm, the pressure of the pressure regulating valve is 0.2-0.5 MPa, the vertical distance between the nozzle and the substrate is 200-400 mm, and the air flow rate of the spray gun is 2-4 m 3 / h, the relative moving speed is 2~2.5m / min, the coating thickness is controlled at 90~120μm, and after two sprayings, a wet film with a thickness of 160~220μm is obtained.
[0016] The spin coating conditions in step (6) refer to that the rotation speed is controlled at 600-800 r / min, the vertical distance between the dropper and the substrate is 50-100 mm, the coating thickness is controlled at 60-80 μm, and after three spin coatings, a wet film with a thickness of 160-220 μm is obtained.
[0017] The surface-treated substrate in step (6) refers to a substrate obtained by one or more methods of sandblasting, electrochemical polishing and mechanical polishing on the surface of the substrate, and the surface roughness thereof is Ra 12.5~Ra 6.3.
[0018] Compared with the prior art, the present invention has the following advantages: 1. The present invention uses transition metal carbide titanium carbide as the main functional filler, with a particle size of 40-100 nm, a NaCl-type cubic structure, and a specific surface area of 65 m 2 / g, volume density is 0.15g / cm 3. Titanium carbide nanoparticles have high melting point, high hardness, high Young's modulus, high chemical stability, wear resistance and corrosion resistance. At the same time, with good electrical and thermal conductivity, titanium carbide nanoparticles can be used as conductive materials to generate Joule heat, and then achieve anti-icing performance on the surface through two-way heat transfer between particles. On the other hand, titanium carbide nanoparticles can be effectively used in photothermal conversion applications due to their unique d-band electronic structure and plasma resonance, which will lead to rapid local heating of their surface. Compared with traditional photothermal materials, titanium carbide nanoparticles are easier to disperse in coatings and have a wider absorption spectrum. The characteristic that their spectral range extends to the near-infrared region is more suitable for applications in the field of anti-icing.
[0019] 2. The present invention uses hollow glass microspheres as the main functional filler, with a particle size of 10-20 μm and a density of 0.12-0.60 g / cm 3 Through hydrothermal reaction, titanium carbide nanoparticles can form titanium carbide-hollow glass microsphere composite functional particles. The composite particles can reduce the mass fraction of titanium carbide nanoparticles in the coating to improve the economy of the coating. At the same time, the large number of hydroxyl groups on the surface provide a basis for the subsequent adsorption of lubricating fluid by the particles and the coupling of the particles into a continuous phase.
[0020] On the other hand, hollow glass microspheres, as a hollow, closed, spherical, powdery, ultra-lightweight filling material, have the advantages of self-lubrication, corrosion resistance, good dispersibility, fluidity, and stability. These intrinsic properties will also improve the corrosion resistance, wear resistance, and thermal insulation performance of the coating surface.
[0021] In addition, the titanium carbide-hollow glass microsphere composite functional particles have light absorption characteristics that are not inferior to those of pure titanium carbide nanoparticles. This is because the titanium carbide nanoparticles grafted on the surface of the hollow glass microspheres will receive sunlight reflected multiple times from the inside of the glass microspheres. Under the hybridization effect of local plasmons, the titanium carbide nanoparticles undergo multiple and stable light absorption processes, making the light absorption rate of the composite particles exceed 88%.
[0022] 3. The titanium carbide-hollow glass microsphere composite functional particles used in the present invention have excellent photothermal and electrothermal composite properties. No additional photothermal or electrothermal functional particles need to be added to the coating, making the production and processing of the coating more cost-effective and environmentally friendly.
[0023] 4. Stearic acid, ethyl orthosilicate and 1H,1H,2H,2H-perfluorododecyltriethoxysilane added in the process of preparing titanium carbide-hollow glass microsphere composite functional particles of the present invention can provide abundant carbon chains and Si-O and CH groups. Under the action of electrostatic interaction and dehydration reaction, they not only promote the assembly of TiC and SiO2 particles, but also reduce the surface energy of the composite functional particles, thus providing a basis for the low surface energy characteristics and low ice adhesion characteristics of the coating surface.
[0024] 5. The lubricating filler and the titanium carbide-hollow glass microsphere composite functional particles in the present invention have excellent adhesion properties, ensuring that the multifunctional coupled super-slip anti-icing coating still maintains low ice adhesion and super-slip properties under multiple deicing cycles. This is because the hollow glass microspheres themselves have lipophilic properties, and the rough surface morphology of the composite particles provides a large number of adsorption sites for the lubricating filler while making the adsorption force between the particles and the lubricating liquid strong. During the coating formation process, the Si-OH group formed by the hydrolysis of the Si-C2H5 group in the silane coupling agent undergoes a condensation reaction with the -OH group on the surface of the glass microsphere. While the titanium carbide-hollow glass microsphere composite functional particles adsorb and fix the lubricating filler, the particles are also connected to each other to form. At the same time, the amino group in the silane coupling agent undergoes a cross-linking reaction with the epoxy group in the epoxy resin, so that the composite particles gradually solidify on the substrate, and finally form a super-slip anti-icing coating with multifunctional coupling such as efficient solar thermal conversion, Joule rapid heating, super-slip, and low ice adhesion.
[0025] 6. The coating surface of the present invention has super-slip properties not only for water, but also for a variety of common liquids in life (such as sewage, coffee, orange juice, salt water, milk, etc.). When the inclination angle is 20°, the slip speed of water on the surface can reach 2cm / s. Figure 5 shown.
[0026] 7. The low ice adhesion property of the coating surface of the present invention has good durability. After multiple deicing-freezing cycles, the ice adhesion force of the coating surface at -20°C and relative humidity exceeding 80% is still less than 15kPa. Figure 6 shown.
[0027] 8. The coating of the present invention has a light absorption rate of >96% in the 0.3-2.5 μm solar band, and has good conductivity and durability. Due to the low surface energy treatment of titanium carbide-hollow glass microsphere composite functional particles in the coating and the role of lubricating fillers, the water rolling angle on the surface of the super-slip anti-icing coating is <5°, and it has self-cleaning, anti-fouling and droplet self-bouncing properties similar to super-hydrophobic surfaces, overcoming the pinning effect limitation of traditional super-hydrophobic deicing surfaces under high humidity conditions.
[0028] 9. The coating of the present invention has good photothermal and electrothermal properties. Through active regulation and control, the coating can achieve precise control of surface temperature under different power density and illumination conditions. For example, when the power density applied to the coating is 0.2W / cm 2 When the light intensity applied to the coating is 1kW / m 2 When the temperature of the coating surface can reach 83°C, the temperature difference between the surface and the environment can reach 67°C. This feature can ensure the active adaptive adjustment of the surface in different environments, thereby solving the problems of overheating and energy waste of the surface, and realizing the low energy consumption and greenness of the multifunctional coupled super-slip anti-icing surface under all-weather conditions.
[0029] 10. The coating of the present invention has strong adaptability and performance stability under corrosive environment, water impact and destructive conditions: when the coating is immersed in 1 mol / L acid, alkali and salt solution environment for 72 hours, the multi-coupling characteristics of the coating surface are still maintained; after the coating is subjected to a strong impact force of 2 m / s for 0.5 hours, there are no residual water droplets on the coating surface, which shows the stability of the super slip on the coating; even if destructive scratches of different widths are engraved on the coating surface, the droplets will still quickly slide off the surface due to the super slip and non-stick characteristics of the coating, which shows the adaptability and durability of the coating in outdoor environment, such as Fig. 9 shown.
[0030] 11. The present invention is simple to operate, has high production efficiency, does not require complicated processing procedures, can be matched with a variety of substrates (copper, stainless steel, aluminum and its alloys, etc.), has a dense coating surface, and has no blistering, cracking and other phenomena. It can be used in aviation and navigation, wind power generation, power transmission, chemical industry, seawater desalination and agricultural equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0032] Figure 1 This is a schematic diagram of the multiple absorption principle of light by the titanium carbide-hollow glass microsphere composite functional particles in the multifunctional coupled super-slip anti-icing coating prepared in Example 1 of the present invention.
[0033] Figure 2 This is a surface morphology of titanium carbide-hollow glass microsphere composite functional particles in the multifunctional coupled super-slip anti-icing coating prepared in Example 2 of the present invention.
[0034] Figure 3 This is the light absorption spectrum of the titanium carbide-hollow glass microsphere composite functional particles in the multifunctional coupled super-slip anti-icing coating prepared in Example 2 of the present invention.
[0035] Figure 4 This is a diagram of the self-cleaning and anti-fouling characteristics of the multifunctional coupled super-slip anti-icing coating prepared in Example 3 of the present invention.
[0036] Figure 5 The super-slip characteristics of the multifunctional coupled super-slip anti-icing coating prepared in Example 3 of the present invention.
[0037] Figure 6 This is a diagram of the low ice adhesion force of the multifunctional coupled super-slip anti-icing coating prepared in Example 3 of the present invention after multiple icing cycles.
[0038] Figure 7 This is a temperature rise diagram of the multifunctional coupled super-slip anti-icing coating prepared in Example 4 of the present invention at different power densities.
[0039] Figure 8 This is a temperature rise diagram of the multifunctional coupled super-slip anti-icing coating prepared in Example 4 of the present invention under different lighting conditions.
[0040] Fig. 9 These are experimental pictures of the multifunctional coupled super slip anti-icing coating (SLAD) prepared in Example 4 of the present invention after corrosion test, water impact test and scratch test. DETAILED DESCRIPTION
[0041] A multifunctional coupled super-slip anti-icing coating is composed of the following raw materials in parts by weight (g): 10-21 parts of titanium carbide nanoparticles, 20-40 parts of epoxy resin, 1-5 parts of stearic acid solution, 10-21 parts of hollow glass microspheres, 1-5 parts of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 1-5 parts of ethyl orthosilicate, 10-20 parts of lubricating filler, 0.1-1 parts of leveling agent, 0.1-1 parts of dispersant, 0.1-1 parts of defoaming agent, 2-4 parts of curing agent, 30-70 parts of solvent and 30-70 parts of anhydrous ethanol solution.
[0042] The coating has a light absorption rate of >96% in the 0.3~2.5μm solar light band and has good conductivity and durability; the water contact angle on the surface of the super-slip anti-icing coating is >100°, the water rolling angle is <5°, and the ice adhesion is <10 kPa.
[0043] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 40~100nm, a cubic crystal form, and a specific surface area of 20~65m 2 / g, volume density is 0.15~0.56g / cm 3 Hollow glass microspheres are inorganic fillers with a particle size of 10-20 μm and a density of 0.12-0.60 g / cm 3 The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 10~50cs.
[0044] The mass concentration of stearic acid solution is 10~20 mmol / L.
[0045] The leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and Efka EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and Efka EFKA2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184.
[0046] The solvent is one or more of anhydrous ethanol, acetone and ethyl acetate.
[0047] A method for preparing a multifunctional coupled super-slip anti-icing coating comprises the following steps: ⑴Weigh according to the ratio.
[0048] (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add titanium carbide nanoparticles, hollow glass microspheres, 1 / 2 of the total amount of stearic acid solution, 2 / 5 of the total amount of ethyl orthosilicate, and 1 / 2 of the total amount of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to anhydrous ethanol solution, stir magnetically at a speed of 400 r / min for 120 to 180 min at room temperature, and perform ultrasonic stirring for 30 to 60 min after stirring to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② Transfer the titanium carbide-hollow glass microsphere composite functional particle suspension to a hydrothermal reactor, the hydrothermal reaction temperature is 180-240°C, the reaction time is 240-360 minutes, and the composite functional particle solution after the hydrothermal reaction is obtained; ③ The composite functional particle solution after the hydrothermal reaction is filtered and the precipitate at the bottom is retained; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained.
[0049] ⑶ Add titanium carbide-hollow glass microsphere composite functional particles, the remaining stearic acid solution, 3 / 10~7 / 5 of the total amount of ethyl orthosilicate, the remaining 1H,1H,2H,2H-perfluorododecyltriethoxysilane, lubricating filler, and 1 / 2 of the total amount of curing agent to 1 / 2 of the total amount of the solvent, and stir at a speed of 600~800r / min for 360~420min to obtain a mixed suspension component A.
[0050] (4) Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, stir at a speed of 400-600 r / min for 120-180 min to obtain a mixed suspension component B.
[0051] (5) Mix the mixed suspension component A with the mixed suspension component B and other components, and add the leveling agent, dispersant, defoaming agent and the remaining curing agent in sequence, and ball mill in a planetary ball mill for 120 to 180 minutes to obtain the super-slip anti-icing suspension solution under all-weather conditions.
[0052] (6) The super-slip anti-icing suspension solution is evenly sprayed or spin-coated on the surface-treated substrate to obtain a wet film with a thickness of 160~220μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3~4 hours to obtain a dry film with a thickness of 100~160μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0053] The spraying conditions are as follows: a low-pressure spray gun with a nozzle diameter of 1.5 mm, a pressure regulating valve pressure of 0.2-0.5 MPa, a vertical distance between the nozzle and the substrate of 200-400 mm, and a spray gun gas flow of 2-4 m 3 / h, the relative moving speed is 2~2.5m / min, the coating thickness is controlled at 90~120μm, and after two sprayings, a wet film with a thickness of 160~220μm is obtained.
[0054] The conditions of spin coating are that the rotation speed is controlled at 600~800r / min, the vertical distance between the dropper and the substrate is 50~100mm, the coating thickness is controlled at 60~80μm, and after three spin coatings, a wet film with a thickness of 160~220μm is obtained.
[0055] The surface treated substrate refers to the substrate surface obtained by one or more methods of sandblasting, electrochemical polishing and mechanical polishing, and its surface roughness is Ra 12.5~Ra 6.3. The substrate can be copper, stainless steel, aluminum and its alloys.
[0056] Example 1 A multifunctional coupled super-slip anti-icing coating is composed of the following raw materials: 10g of titanium carbide nanoparticles, 20g of epoxy resin, 1g of stearic acid solution, 10g of hollow glass microspheres, 1g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 1g of tetraethyl orthosilicate, 10g of lubricating filler, 0.1g of leveling agent, 0.1g of dispersant, 0.1g of defoaming agent, 2g of curing agent, 30g of solvent and 30g of anhydrous ethanol solution.
[0057] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 40nm, a cubic crystal form, and a specific surface area of 65m2 / g, volume density is 0.15g / cm 3 Hollow glass microspheres are inorganic fillers with a particle size of 10 μm and a density of 0.12 g / cm 3 ; The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 10cs.
[0058] The mass concentration of the stearic acid solution is 10 mmol / L.
[0059] The leveling agent is Digo Glide 450 silicone leveling agent; the dispersant is Digo TEGO755W; the defoaming agent is Digo TEGO 901W polyether siloxane defoaming agent; and the curing agent is KH550.
[0060] The solvent is anhydrous ethanol.
[0061] The preparation method thereof comprises the following steps: ⑴Weigh according to the ratio.
[0062] (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add 10g of titanium carbide nanoparticles, hollow glass microspheres, 0.5g of stearic acid solution, 0.4g of ethyl orthosilicate, and 0.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 30g of anhydrous ethanol solution, stir magnetically at a speed of 400r / min for 120min at room temperature, and then ultrasonicate for 30min to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② Transfer the titanium carbide-hollow glass microsphere composite functional particle suspension to a hydrothermal reactor, the hydrothermal reaction temperature is 180°C, the reaction time is 240 min, and the composite functional particle solution after the hydrothermal reaction is obtained; ③ The composite functional particle solution after the hydrothermal reaction is filtered and the precipitate at the bottom is retained; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained.
[0063] Figure 1 This is a schematic diagram of the multiple light absorption principle on the surface of the prepared titanium carbide-hollow glass microsphere composite functional particles, indicating that the composite functional particles can achieve the economy of the coating without reducing the light and heat absorption and conversion performance of the coating.
[0064] ⑶ Add 10g of titanium carbide-hollow glass microsphere composite functional particles, 0.5g of stearic acid solution, 0.3g of ethyl orthosilicate, 0.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, lubricating filler, and 1.0g of curing agent to 15g of solvent, and stir at a speed of 600r / min for 360min to obtain a mixed suspension component A.
[0065] (4) Add epoxy resin and 0.3 g of ethyl orthosilicate to 15 g of solvent, and stir at a speed of 400 r / min for 120 min to obtain a mixed suspension component B.
[0066] (5) Mix the mixed suspension component A with the mixed suspension component B and other components, and add the leveling agent, dispersant, defoaming agent and 1.0g curing agent in sequence, and ball mill in a planetary ball mill for 120 minutes to obtain the super slip anti-icing suspension solution under all-weather conditions.
[0067] ⑹ Evenly spray or spin-coat 10 g of the super-slip anti-icing suspension solution on the surface-treated substrate to obtain a wet film with a thickness of 160 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3 hours to obtain a dry film with a thickness of 100 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0068] The spraying conditions are as follows: a low-pressure spray gun with a nozzle diameter of 1.5 mm, a pressure regulating valve pressure of 0.2 MPa, a vertical distance between the nozzle and the substrate of 200 mm, and a spray gun gas flow rate of 2 m 3 / h, the relative moving speed is 2m / min, the coating thickness is controlled at 90μm, and after two sprayings, a wet film with a thickness of 160μm is obtained.
[0069] The conditions of spin coating are that the rotation speed is controlled at 600 r / min, the vertical distance between the dropper and the substrate is 50 mm, the coating thickness is controlled at 60 μm, and a wet film with a thickness of 160 μm is obtained after three spin coatings.
[0070] The solar absorptivity of the coating was evaluated using a Lambda 950 UV / visible / near-infrared spectrophotometer (equipped with a 150 mm integrating sphere) manufactured by PerkinElmer, USA, and its absorptivity in the 0.3-2.5 μm band was measured. The solar absorptivity was then calculated according to the calculation formula in the international standard ISO 9845-1 (1992). The solar absorptivity of the coating prepared in Example 1 in the 0.3-2.5 μm band was measured to be 0.966.
[0071] The water contact angle and water sliding angle of the surface were characterized by an angular contact meter (JY-PHb). The volume of the test water droplet was 10 μL. The water contact angle of the coating prepared in Example 1 was measured to be 103°, and the water sliding angle was 4.3°.
[0072] The ice cubes on the surface were tested using a thrust tester (HEMUELE), and then the adhesion force calculation formula ( ) was tested for ice adhesion, and the ice adhesion of the coating prepared in Example 1 was measured to be 5.2 kPa.
[0073] Example 2 A multifunctional coupled super-slip anti-icing coating is composed of the following raw materials: 15g of titanium carbide nanoparticles, 20g of epoxy resin, 3g of stearic acid solution, 15g of hollow glass microspheres, 2g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 3g of tetraethyl orthosilicate, 10g of lubricating filler, 0.1g of leveling agent, 0.1g of dispersant, 0.1g of defoaming agent, 2g of curing agent, 60g of solvent and 45g of anhydrous ethanol solution.
[0074] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 50nm, a cubic crystal form, and a specific surface area of 38.7m 2 / g, volume density is 0.28g / cm 3 Hollow glass microspheres are inorganic fillers with a particle size of 10 μm and a density of 0.12 g / cm 3 ; The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 20cs.
[0075] The mass concentration of the stearic acid solution is 10 mmol / L.
[0076] The leveling agent is AFCONA 3777 fluorocarbon modified polyacrylate leveling agent; the dispersant is TEGO 662 C; the defoamer is EFKA 2720 unsaturated polyester defoamer; and the curing agent is SYLGARD184.
[0077] The solvent is acetone.
[0078] The preparation method thereof comprises the following steps: ⑴Weigh according to the ratio.
[0079] (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add 15g of titanium carbide nanoparticles, hollow glass microspheres, 1.5g of stearic acid solution, 1.2g of ethyl orthosilicate, and 1g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 45g of anhydrous ethanol solution, stir magnetically at a speed of 400r / min for 120min at room temperature, and then stir and ultrasonicate for 60min to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② Transfer the titanium carbide-hollow glass microsphere composite functional particle suspension to a hydrothermal reactor, the hydrothermal reaction temperature is 200°C, the reaction time is 240 min, and the composite functional particle solution after the hydrothermal reaction is obtained; ③ The composite functional particle solution after the hydrothermal reaction is filtered and the precipitate at the bottom is retained; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained.
[0080] Figure 2 This is a morphology image of the surface of the prepared titanium carbide-hollow glass microsphere composite functional particles, indicating that the hollow glass microspheres and titanium carbide nanoparticles were successfully prepared into titanium carbide-hollow glass microsphere composite functional particles under hydrothermal reaction, and there was no agglomeration or breakage between the composite particles.
[0081] Figure 3 This is the light absorption spectrum of the titanium carbide-hollow glass microsphere composite functional particles in the prepared multifunctional coupled super-slip anti-icing coating, which shows that the titanium carbide-hollow glass microsphere composite functional particles inherit the intrinsic light absorption characteristics of titanium carbide particles, and under the multiple reflections of the hollow glass microspheres, the light absorption spectrum width of the particles is further widened.
[0082] ⑶ Add 10g of titanium carbide-hollow glass microsphere composite functional particles, 1.5g of stearic acid solution, 1.0g of ethyl orthosilicate, 1g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, lubricating filler, and 1g of curing agent to 30g of solvent, and stir at a speed of 600r / min for 360min to obtain a mixed suspension component A.
[0083] (4) Add epoxy resin and 0.8 g of tetraethyl orthosilicate to 30 g of solvent, stir at a speed of 600 r / min for 120 min, and prepare a mixed suspension component B.
[0084] (5) Mix the mixed suspension component A with the mixed suspension component B and other components, and add the leveling agent, dispersant, defoaming agent and 1g curing agent in sequence, and ball mill in a planetary ball mill for 120 minutes to obtain the super-slip anti-icing suspension solution under all-weather conditions.
[0085] (6) Spray or spin-coat 20 g of the super-slip anti-icing suspension solution evenly on the surface-treated substrate to obtain a wet film with a thickness of 160 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3 to 4 hours to obtain a dry film with a thickness of 100 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0086] The spraying conditions are as follows: a low-pressure spray gun with a nozzle diameter of 1.5 mm, a pressure regulating valve pressure of 0.2 MPa, a vertical distance between the nozzle and the substrate of 200 mm, and a spray gun gas flow rate of 2 m 3 / h, the relative moving speed is 2m / min, the coating thickness is controlled at 90μm, and after two sprayings, a wet film with a thickness of 160μm is obtained.
[0087] The conditions of spin coating are that the rotation speed is controlled at 600 r / min, the vertical distance between the dropper and the substrate is 80 mm, the coating thickness is controlled at 60 μm, and a wet film with a thickness of 160 μm is obtained after three spin coatings.
[0088] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 2 in the 0.3-2.5 μm band was measured to be 0.971, the water contact angle was 106.1°, the water sliding angle was 3.7°, and the ice adhesion of the coating was 4.2 kPa.
[0089] Example 3 A multifunctional coupled super-slip anti-icing coating is composed of the following raw materials: 15g of titanium carbide nanoparticles, 25g of epoxy resin, 3g of stearic acid solution, 15g of hollow glass microspheres, 4g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 3g of tetraethyl orthosilicate, 15g of lubricating filler, 0.5g of leveling agent, 0.5g of dispersant, 0.5g of defoaming agent, 2.5g of curing agent, 70g of solvent and 50g of anhydrous ethanol solution.
[0090] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 80nm, a cubic crystal form, and a specific surface area of 32m 2 / g, volume density is 0.41g / cm 3 Hollow glass microspheres are inorganic fillers with a particle size of 15 μm and a density of 0.35 g / cm 3 ; The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 30cs.
[0091] The mass concentration of stearic acid solution is 15 mmol / L.
[0092] The leveling agent is AFCONA 3034; the dispersant is EFKA 5065; the defoaming agent is TEGO901W polyether siloxane defoaming agent; and the curing agent is SYLGARD 184.
[0093] The solvent was ethyl acetate.
[0094] The preparation method thereof comprises the following steps: ⑴Weigh according to the ratio.
[0095] (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add titanium carbide nanoparticles, hollow glass microspheres, 1.5 g stearic acid solution, 1.2 g ethyl orthosilicate, and 2 g 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 50 g anhydrous ethanol solution, stir magnetically at 400 r / min for 180 min at room temperature, and then ultrasonicate for 30 min to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② Transfer the titanium carbide-hollow glass microsphere composite functional particle suspension to a hydrothermal reactor, the hydrothermal reaction temperature is 240°C, the reaction time is 300 min, and the composite functional particle solution after the hydrothermal reaction is obtained; ③ The composite functional particle solution after the hydrothermal reaction is filtered and the precipitate at the bottom is retained; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained.
[0096] ⑶ Add 15g of titanium carbide-hollow glass microsphere composite functional particles, 1.5g of stearic acid solution, 1.0g of ethyl orthosilicate, 2g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, a lubricating filler, and 1.25g of a curing agent to 35g of a solvent, and stir at a speed of 800r / min for 420min to obtain a mixed suspension component A.
[0097] (4) Add epoxy resin and 0.8 g of tetraethyl orthosilicate to 35 g of solvent, and stir at a speed of 600 r / min for 180 min to obtain a mixed suspension component B.
[0098] (5) Mix the mixed suspension component A with the mixed suspension component B and other components, and add the leveling agent, dispersant, defoaming agent and 1.25g curing agent in sequence, and ball mill for 180 minutes in a planetary ball mill to obtain the super slip anti-icing suspension solution under all-weather conditions.
[0099] (6) Evenly spray or spin-coat 15 g of the super-slip anti-icing suspension solution on the surface-treated substrate to obtain a wet film with a thickness of 190 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3 to 4 hours to obtain a dry film with a thickness of 120 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0100] The spraying conditions are as follows: a low-pressure spray gun with a nozzle diameter of 1.5 mm, a pressure regulating valve pressure of 0.3 MPa, a vertical distance between the nozzle and the substrate of 300 mm, and a spray gun gas flow rate of 3 m 3 / h, the relative moving speed is 2.2m / min, the coating thickness is controlled at 100μm, and a wet film with a thickness of 190μm is obtained after two sprayings.
[0101] The conditions of spin coating are that the rotation speed is controlled at 700 r / min, the vertical distance between the dropper and the substrate is 80 mm, the coating thickness is controlled at 70 μm, and a wet film with a thickness of 190 μm is obtained after three spin coatings.
[0102] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 3 in the 0.3-2.5 μm band was measured to be 0.975, the water contact angle was 104.4°, the water sliding angle was 3.9°, and the ice adhesion of the coating was 6.9 kPa.
[0103] Figure 4 This is a diagram of the self-cleaning and anti-fouling properties of the prepared multifunctional coupled super-slip anti-icing coating, which shows that under the coupling of the non-stick and super-slip properties of the coating, the coating surface has properties similar to a super-hydrophobic surface, which expands the application scenarios and environmental adaptability of the multifunctional coupled super-slip anti-icing coating in outdoor environments.
[0104] Figure 5 The super-slip properties of the prepared multifunctional coupled super-slip anti-icing coating at an inclination angle of 20° show that the coating has non-stick and super-slip properties for a variety of solutions, especially the super-slip properties for aqueous solutions, and its slip speed on the surface can reach 2cm / s. Therefore, the coating has anti-icing and anti-adhesion properties suitable for a variety of solution systems.
[0105] Figure 6 This is a graph showing the low ice adhesion characteristics of the multifunctional coupled super-slip anti-icing coating prepared after multiple deicing-icing cycle tests at a temperature of -20°C and a relative humidity of 80%. It shows that the prepared coating has obvious advantages in low ice adhesion characteristics compared with ordinary porous infiltration super-slip coatings (PSAD) and ordinary super-hydrophobic anti-icing coatings (PLAD). After multiple cycle tests, the ice adhesion force on the coating surface is still less than 15kPa.
[0106] Example 4 A multifunctional coupled super-slip anti-icing coating is composed of the following raw materials: 21g of titanium carbide nanoparticles, 40g of epoxy resin, 5g of stearic acid solution, 21g of hollow glass microspheres, 5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 5g of tetraethyl orthosilicate, 20g of lubricating filler, 1g of leveling agent, 1g of dispersant, 1g of defoaming agent, 4g of curing agent, 70g of solvent and 70g of anhydrous ethanol solution.
[0107] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 100nm, a cubic crystal form, and a specific surface area of 20m 2 / g, volume density is 0.56g / cm3 Hollow glass microspheres are inorganic fillers with a particle size of 20 μm and a density of 0.6 g / cm 3 ; The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 50cs.
[0108] The mass concentration of the stearic acid solution is 20 mmol / L.
[0109] The leveling agent is AFCONA 3777 fluorocarbon modified polyacrylate leveling agent; the dispersant is EFKA 5065; the defoaming agent is EFKA 2720 unsaturated polyester defoaming agent; and the curing agent is SYLGARD184.
[0110] The solvent is a mixed solution of ethyl acetate and anhydrous ethanol with a mass ratio (g / g) of 5:2.
[0111] The preparation method thereof comprises the following steps: ⑴Weigh according to the ratio.
[0112] (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add 21g of titanium carbide nanoparticles, hollow glass microspheres, 2.5g of stearic acid solution, 2g of ethyl orthosilicate, and 2.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 70g of anhydrous ethanol solution, stir magnetically at a speed of 400r / min for 180min at room temperature, and then stir and ultrasonicate for 60min to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② Transfer the titanium carbide-hollow glass microsphere composite functional particle suspension to a hydrothermal reactor, the hydrothermal reaction temperature is 240°C, the reaction time is 360 min, and the composite functional particle solution after the hydrothermal reaction is obtained; ③ The composite functional particle solution after the hydrothermal reaction is filtered and the precipitate at the bottom is retained; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained.
[0113] ⑶ Add 20g of titanium carbide-hollow glass microsphere composite functional particles, 2.5g of stearic acid solution, 1.75g of ethyl orthosilicate, 2.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, a lubricating filler, and 2g of a curing agent to 35g of a solvent, and stir at a speed of 800r / min for 420min to obtain a mixed suspension component A.
[0114] (4) Add epoxy resin and 1.25 g of ethyl orthosilicate to 35 g of solvent, and stir at a speed of 600 r / min for 180 min to obtain a mixed suspension component B.
[0115] (5) Mix the mixed suspension component A with the mixed suspension component B and other components, and add the leveling agent, dispersant, defoaming agent and 2g curing agent in sequence, and ball mill for 180 minutes in a planetary ball mill to obtain the super slip anti-icing suspension solution under all-weather conditions.
[0116] (6) Evenly spray or spin-coat 12 g of the super-slip anti-icing suspension solution on the surface-treated substrate to obtain a wet film with a thickness of 220 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3 to 4 hours to obtain a dry film with a thickness of 160 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
[0117] The spraying conditions are as follows: a low-pressure spray gun with a nozzle diameter of 1.5 mm, a pressure regulating valve pressure of 0.5 MPa, a vertical distance between the nozzle and the substrate of 400 mm, and a spray gun gas flow rate of 4 m 3 / h, the relative moving speed is 2.5m / min, the coating thickness is controlled at 120μm, and after two sprayings, a wet film with a thickness of 220μm is obtained.
[0118] The conditions of spin coating are that the rotation speed is controlled at 800 r / min, the vertical distance between the dropper and the substrate is 100 mm, the coating thickness is controlled at 80 μm, and a wet film with a thickness of 220 μm is obtained after three spin coatings.
[0119] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 4 in the 0.3-2.5 μm band was measured to be 0.974, the water contact angle was 103.8°, the water sliding angle was 4.1°, and the ice adhesion of the coating was 7.2 kPa.
[0120] Figure 7 The surface temperature rise diagram of the prepared multifunctional coupled super-slip anti-icing coating at different power densities shows that the coating has good Joule heating characteristics at different power densities, and this characteristic also has excellent adjustable and controllable characteristics. While saving electric energy, it can also be used for anti-icing and thermal insulation needs in different environments.
[0121] Figure 8 This is the surface temperature rise diagram of the prepared multifunctional coupled super-slip anti-icing coating under different lighting conditions, which shows that the coating has fast and efficient light absorption and heat conversion characteristics under different lighting conditions, ensuring the photothermal properties of the coating under a variety of climatic conditions.
[0122] Fig. 9The experimental pictures of the prepared multifunctional coupled super-slip anti-icing coating (SLAD) after corrosion test, water impact test and scratch test respectively show that: after the coating is immersed in 1 mol / L acid, alkali and salt solution environment for 72 hours, there is no obvious chemical reaction on the coating surface, proving that the coating surface has excellent chemical inertness and corrosion resistance in the corrosive environment; after the coating is impacted by water flow velocity of 2 m / s for 0.5 hours, there are no residual water droplets on the coating surface, indicating the stability of the super-slip property of the coating; after destructive scratches are made on the coating, the droplets will still slide off the surface quickly due to the super-slip and non-stick properties of the coating, indicating the adaptability and durability of the coating in outdoor environment. This also provides a guarantee for the multifunctional coupling characteristics of the coating surface under complex application conditions.
Claims
1. A multifunctional coupled super-slip anti-icing coating, characterized in that: The coating is composed of the following raw materials in parts by weight: 10-21 parts of titanium carbide nanoparticles, 20-40 parts of epoxy resin, 1-5 parts of stearic acid solution, 10-21 parts of hollow glass microspheres, 1-5 parts of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 1-5 parts of ethyl orthosilicate, 10-20 parts of lubricating filler, 0.1-1 parts of leveling agent, 0.1-1 parts of dispersant, 0.1-1 parts of defoaming agent, 2-4 parts of curing agent, 30-70 parts of solvent and 30-70 parts of anhydrous ethanol solution.
2. The multifunctional coupled super-slip anti-icing coating according to claim 1, characterized in that: The titanium carbide nanoparticles are transition metal carbides with a particle size of 40-100 nm, a cubic crystal form, and a specific surface area of 20-65 m 2 / g, volume density is 0.15~0.56g / cm 3 The hollow glass microspheres are inorganic fillers with a particle size of 10-20 μm and a density of 0.12-0.60 g / cm 3 The lubricating filler is dimethyl silicone oil or liquid paraffin with a viscosity of 10~50 cs.
3. The multifunctional coupled super-slip anti-icing coating according to claim 1, characterized in that: The mass concentration of the stearic acid solution is 10-20 mmol / L.
4. The multifunctional coupled super-slip anti-icing coating according to claim 1, characterized in that: The leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and EFKA 2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184.
5. The multifunctional coupled super-slip anti-icing coating according to claim 1, characterized in that: The solvent is one or more of anhydrous ethanol, acetone and ethyl acetate.
6. The multifunctional coupled super-slip anti-icing coating according to claim 1, characterized in that: The light absorption rate of the coating in the 0.3~2.5μm solar light band is >96%, and the water contact angle of the coating surface is >100°, the water rolling angle is <5°, and the ice adhesion is <10 kPa.
7. The method for preparing a multifunctional coupled super-slip anti-icing coating according to claim 1, comprising the following steps: ⑴Weigh according to the ratio; (2) Preparation of titanium carbide-hollow glass microsphere composite functional particles: ① Add titanium carbide nanoparticles, hollow glass microspheres, 1 / 2 of the total amount of stearic acid solution, 2 / 5 of the total amount of ethyl orthosilicate, and 1 / 2 of the total amount of 1H,1H,2H,2H-perfluorododecyltriethoxysilane to anhydrous ethanol solution, stir magnetically at a speed of 400 r / min for 120 to 180 min at room temperature, and perform ultrasonic stirring for 30 to 60 min after stirring to obtain a uniformly distributed titanium carbide-hollow glass microsphere composite functional particle suspension; ② The titanium carbide-hollow glass microsphere composite functional particle suspension is transferred to a hydrothermal reaction kettle, the hydrothermal reaction temperature is 180-240° C., and the reaction time is 240-360 min, to obtain a composite functional particle solution after the hydrothermal reaction; ③ The composite functional particle solution after the hydrothermal reaction is filtered to retain the precipitate at the bottom; the precipitate is rinsed with anhydrous ethanol and dried; after 5 rinse-drying cycles, titanium carbide-hollow glass microsphere composite functional particles are obtained; ⑶ Add titanium carbide-hollow glass microsphere composite functional particles, the remaining stearic acid solution, 3 / 10-7 / 5 of the total amount of ethyl orthosilicate, the remaining 1H,1H,2H,2H-perfluorododecyltriethoxysilane, lubricating filler, and 1 / 2 of the total amount of curing agent to 1 / 2 of the total amount of the solvent, and stir at a speed of 600-800 r / min for 360-420 min to obtain a mixed suspension component A; (4) Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, stir at a speed of 400-600 r / min for 120-180 min to obtain a mixed suspension component B; (5) Mixing the mixed suspension component A with the mixed suspension component B and other components, and sequentially adding a leveling agent, a dispersant, a defoaming agent, and the remaining curing agent, and ball milling in a planetary ball mill for 120 to 180 minutes to obtain an ultra-slip anti-icing suspension solution under all-weather conditions; (6) The super-slip anti-icing suspension solution is evenly sprayed or spin-coated on the surface-treated substrate to obtain a wet film with a thickness of 160-220 μm; the wet film is cured at room temperature for 10 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 100-160 μm, which is a multifunctional coupled super-slip anti-icing coating for use under all-weather conditions.
8. The method for preparing a multifunctional coupled super-slip anti-icing coating according to claim 7, characterized in that: The spraying conditions in step (6) are as follows: a low-pressure spray gun is used with a nozzle diameter of 1.5 mm, the pressure of the pressure regulating valve is 0.2-0.5 MPa, the vertical distance between the nozzle and the substrate is 200-400 mm, and the air flow rate of the spray gun is 2-4 m 3 / h, the relative moving speed is 2~2.5m / min, the coating thickness is controlled at 90~120μm, and after two sprayings, a wet film with a thickness of 160~220μm is obtained.
9. The method for preparing a multifunctional coupled super-slip anti-icing coating according to claim 7, characterized in that: The spin coating conditions in step (6) refer to that the rotation speed is controlled at 600-800 r / min, the vertical distance between the dropper and the substrate is 50-100 mm, the coating thickness is controlled at 60-80 μm, and after three spin coatings, a wet film with a thickness of 160-220 μm is obtained.
10. The method for preparing a multifunctional coupled super-slip anti-icing coating according to claim 7, characterized in that: The surface-treated substrate in step (6) refers to a substrate obtained by one or more methods of sandblasting, electrochemical polishing and mechanical polishing on the surface of the substrate, and the surface roughness thereof is Ra 12.5~Ra 6.3.
Citation Information
Patent Citations
Coating material for preparing super-slippage coating and application of coating material
CN113801535A
Electric-heating self-lubricating ice-prevention and deicing coating as well as preparation method and application thereof
CN109486332A
Super-hydrophobic coating with photo-thermal deicing and long-acting corrosion resistance and preparation method
CN115044297A
Hollow microsphere composite heat-conducting filler coated with low-dimensional nano high-heat-conductivity material as well as preparation method and application of hollow microsphere composite heat-conducting filler
CN115612179A
Magnesium alloy surface self-healing anti-icing coating and preparation method thereof
CN117701123A
